2012
DOI: 10.2174/156800912801784875
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles for Modulation of microRNA Signatures in Cancer Chemoprevention

Abstract: miRNAs are small endogenous non-coding RNAs, approximately 21-nucleotides in length, which are shown to regulate an array of cellular processes such as differentiation, cell cycle, cell proliferation, apoptosis, and angiogenesis which are important in cancer. miRNAs can function as both tumor promoters (oncomiRs) or tumor suppressors by their ability to target numerous biomolecules that are important in carcinogenesis. Aberrant expression of miRNAs is correlated with the development and progression of tumors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…It has emerged as an important gene regulators being critically involved in carcinogenesis and cancer chemoprevention [11][12][13][14]. miR-34a is a star molecule and has been found to participate in the regulation of p53 pathways as well as the tumour suppressor activity [15][16][17], miR-34a becomes more and more important and could be a good clue to discover some unknown field.…”
Section: Introductionmentioning
confidence: 99%
“…It has emerged as an important gene regulators being critically involved in carcinogenesis and cancer chemoprevention [11][12][13][14]. miR-34a is a star molecule and has been found to participate in the regulation of p53 pathways as well as the tumour suppressor activity [15][16][17], miR-34a becomes more and more important and could be a good clue to discover some unknown field.…”
Section: Introductionmentioning
confidence: 99%
“…[9293] Different cancer studies have shown that miRNAs interact with genes in diverse cellular pathways, resulting in differential gene expression profiles of normal and tumor tissues and among tumor types. [8294] For instance, miRNAs such as miR-221 and miR-22 are highly expressed in different cancers (e.g.…”
Section: Future and Novel Targets For Tchmmentioning
confidence: 99%
“…The number of new cases is expected to rise by about 70% over the next two decades [1]. As the incidence of cancer is increasing, the new modalities of treatments have also become more significant [2].…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy is one of the primary therapeutic regimens for treating cancer [2,3]. Common side effects of chemotherapy include fatigue, alopecia, anemia, easy bruising, diarrhea, constipation, alteration in taste, and appetite.…”
Section: Introductionmentioning
confidence: 99%